Are NTU Bachelor of Accountancy undergraduates equipped for assurance services? - Koh, Hwee Ling. (2008)
This research evaluates if the NTU BAcc curriculum structure helps students to develop the relevant competencies for providing assurance services. It also identifies areas for curriculum improvement and suggests recommendations to enhance the curriculum, aiming to propel NTU towards world-class standards.